Pemberian Hak Asuh Anak Belum Mumayiz Kepada Ayah Pasca Perceraian dalam Perspektif Hukum Islam - Zakiyyah, Nisrina Maitsa; Eka; Hendra Karunia Agustine (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2026)
Custody of a child who has not yet reached the age of discernment (mumayyiz) after divorce is not always granted to the mother if the judge of the Religious Court has a different opinion. In some cases, the father can obtain custody even though the mother is still present. Such is the case in the Religious Court of Sumber Decree Number 2083/Pdt.G/2023/PA.Sbr, where the panel of judges granted custody of the first child, aged 11, to the father, despite no specific reasons being found during the trial to indicate that the mother was unfit to hold custody. The purpose of this research is to find out why custody of a non-mumayyiz child after divorce was granted to the father in the Religious Court of Sumber Decree Number 2083/Pdt.G/2023/PA.Sbr, as well as to analyze it from the perspective of Islamic law. This study uses a qualitative method with a descriptive approach and a case study design. The analysis was conducted by reducing data, presenting data, and drawing conclusions. The results of the study show that the granting of custody of a non-mumayyiz child to the father after divorce in the Religious Court of Sumber Decree Number 2083/Pdt.G/2023/PA.Sbr was due to the child’s closer emotional bond with the father, as the child had been cared for by the father for some time. In Islamic law, as long as the mother is still alive and fit to care for the child, she is more entitled to custody. However, in this case, the judge considered the specific circumstances, so granting custody to the father was deemed in line with the primary goal of hadlanah, which is to uphold the child’s best interests and welfare.